Already have an account? Get multiple benefits of using own account!
Login in your account..!
Remember me
Don't have an account? Create your account in less than a minutes,
Forgot password? how can I recover my password now!
Enter right registered email to receive password!
Need Solution
Find (dy)/( dx) for;
(i). y = x7
(ii). y = x2γ
(iii). y = x-3
(iv). y = x
#question.
Dawn wants to evaluate the volume of a basketball along with the volume of a tennis ball. Which formula will she use? The volume of a sphere is 4/3 times π times the radius cub
an insurance salesman sells policies to 5 men, all of identical age in good health. the probability that a man of this particular age will be alive 20 years hence is 2/3.Find the p
Find all the local maximum and minimum values and saddle points of the function f(x, y) = x 2 - xy + y 2 + 9x - 6y + 10
1. Write two m-files, one for the bisection method and another for Newton's method. 2. Using both the Bisection method and the Newton method answer the following: Include th
a child prepares a poster to save energy on a square sheet whose each side measures 50 cm . At each corner she draws a quadrant of radius 5 cm and the centre of a circle of diamete
the automatic hopper loader is set to put 36 tons of coal in each car. the actual weights of coal loaded into each car arw normally distributed with a mean of 36 tons and a standar
Saddle Point This point in a pay off matrix is one which is the largest value in its column and the smallest value in its row. This is also termed as equilibrium point in the t
Critical point of exponential functions and trig functions, Let's see some examples that don't just involve powers of x. Example: find out all the critical points for the
marketing plan for new product
Solution i. y = x7 (dy)/( dx) = 7x 7-1 = 7x6 ii. y = x2? (dy)/(dx) = 2γ x(2γ- 1) iii. y = x-3 (dy)/(dx) = -3x-3-1 = -3x-4 vi. y = x (dy)/( dx) = 1x1-1 = 1.x0= 1 (since x0=1)
Solution
i. y = x7
(dy)/( dx) = 7x 7-1 = 7x6
ii. y = x2?
(dy)/(dx) = 2γ x(2γ- 1)
iii. y = x-3
(dy)/(dx) = -3x-3-1 = -3x-4
vi. y = x
(dy)/( dx) = 1x1-1 = 1.x0= 1 (since x0=1)
Get guaranteed satisfaction & time on delivery in every assignment order you paid with us! We ensure premium quality solution document along with free turntin report!
whatsapp: +1-415-670-9521
Phone: +1-415-670-9521
Email: [email protected]
All rights reserved! Copyrights ©2019-2020 ExpertsMind IT Educational Pvt Ltd